2021
DOI: 10.3390/v13020346
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of HBV Genotype B and HDV Genotype 1 in Vietnamese Patients with Chronic Hepatitis

Abstract: Hepatitis delta virus (HDV) coinfection will additionally aggravate the hepatitis B virus (HBV) burden in the coming decades, with an increase in HBV-related liver diseases. Between 2018 and 2019, a total of 205 HBV patients clinically characterized as chronic hepatitis B (CHB; n = 115), liver cirrhosis (LC; n = 21), and hepatocellular carcinoma (HCC; n = 69) were recruited. HBV surface antigen (HBsAg), antibodies against surface antigens (anti-HBs), and core antigens (anti-HBc) were determined by ELISA. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…In the present study, in a study population of 623 HBsAg-negative blood donors from Hanoi, we found an OBI prevalence of 0.3%, which is low compared to the number of cases reported in a literature review for Asia (0.013-5.5%) [27,31]. This is noteworthy considering the fact that Vietnam is highly endemic for HBV [19,22], which is confirmed by the high seroprevalence of HBV markers found in this study. In fact, 73% of our samples tested positive for at least one HBV antibody (anti-HBs and anti-HBc), with 39% being positive for anti-HBc.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In the present study, in a study population of 623 HBsAg-negative blood donors from Hanoi, we found an OBI prevalence of 0.3%, which is low compared to the number of cases reported in a literature review for Asia (0.013-5.5%) [27,31]. This is noteworthy considering the fact that Vietnam is highly endemic for HBV [19,22], which is confirmed by the high seroprevalence of HBV markers found in this study. In fact, 73% of our samples tested positive for at least one HBV antibody (anti-HBs and anti-HBc), with 39% being positive for anti-HBc.…”
Section: Discussionsupporting
confidence: 74%
“…After nested PCR, amplicons were purified and sequenced. BLAST searches against the NCBI database revealed that the two OBI cases belonged to HBV genotype B, which is predominant in Vietnam [21][22][23]. A phylogenetic tree was then constructed using the sequences of the two OBI positive samples and 52 representative S/preS HBV sequences of A-H genotypes from the HBV database (HBVdb), which showed the two OBI positive samples clustering with genotype group B, consistent with the BLAST search results (Figure 3).…”
Section: Obi Genotypingsupporting
confidence: 63%
See 2 more Smart Citations
“…HBV genotyping was determined by amplification and sequencing of 332 bp of HBV S gene using nested PCR reaction as described previously. 21 , 22 Briefly, the first PCR was carried out using the primer pairs HBV-022 (sense primer) and antisense primers HBV-065 and HBV-066. The nested reaction was performed primers HBV-024 (sense primer) and antisense primers HBV-041 and HBV-064.…”
Section: Determination Of Hbv Genotype and S Gene Mutationsmentioning
confidence: 99%